2006
DOI: 10.1097/01.nmd.0000217821.18908.bf
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation, Resting EEG, and Subjective Sleep Experiences in Undergraduates

Abstract: In this study, we explored whether individual differences in dissociation are related to certain resting electroencephalographic (EEG) parameters. Baseline EEG with eyes open and closed was recorded in an undergraduate sample (N = 67). Cortical power in the alpha range was inversely related to dissociative symptoms as measured by the Dissociative Experiences Scale, while both delta and theta power where positively related to dissociation. However, sleep experiences, as indexed with the Iowa Sleep Experiences S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 50 publications
3
21
0
Order By: Relevance
“…These findings corroborate with previous studies that have suggested an association of mediumistic and spirit possession experiences with greater theta and beta power 18,19 , as well as an association of dissociation with greater theta power 9,10 . However, contrary to the cases reported by Oohashi et al 19 and Delorme et al 18 , we found no between-group difference in alpha power during the mediumistic communication.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings corroborate with previous studies that have suggested an association of mediumistic and spirit possession experiences with greater theta and beta power 18,19 , as well as an association of dissociation with greater theta power 9,10 . However, contrary to the cases reported by Oohashi et al 19 and Delorme et al 18 , we found no between-group difference in alpha power during the mediumistic communication.…”
Section: Discussionsupporting
confidence: 82%
“…Likewise, both in pathological and non-pathological contexts, EEG theta activity was positively correlated with DES (Dissociative Experiences Scale) scores 9,10 . The coherence is a measure that quantifies the covariation of power spectra within specific frequency bands among pairs of EEG electrodes, being an index of synchronization between cortical areas.…”
Section: Introductionmentioning
confidence: 89%
“…Several studies have found that the DES correlates significantly with the ISES General Sleep Experiences scale ( r s ranging from .35 to .55), although not with the ISES Lucid Dreaming scale ( r s ranging from .08 to .23) (Fassler, Knox, & Lynn, 2006; Giesbrecht, Jongen, Smulders, & Merckelbach, 2006; Giesbrecht & Merckelbach, 2004, 2006). Similarly, Knox (2008) found that the ISES General Sleep Experiences scale was significantly related to dissociation and the positive symptoms of schizotypy as measured by the DES and the Perceptual Aberration and Magical Ideation scales; however, the ISES General Sleep Experiences scale was not significantly related to the negative symptoms of schizotypy as measured by the Revised Social Anhedonia scale, and the ISES Lucid Dreaming scale was not significantly related to schizotypy and dissociation.…”
Section: Unusual Sleep Experiencesmentioning
confidence: 99%
“…QEEG changes relating to dissociative trait experiences have only rarely been demonstrated: an association between trait dissociation and theta power in undergraduate students (Giesbrecht, Jongen, Smulders, & Merckelbach, 2006) and in patients with borderline personality disorder who felt no pain during a cold pressor test (Russ, Campbell, Kakuma, Harrison, & Zanine, 1999); increased theta power in highly hypnotizable students, -4 -especially during hypnosis (Sabourin, Cutcomb, Crawford, & Pribram, 1990); and increased beta, alpha or delta power in patients with multiple personality disorder during induction of alter personalities (Cocker, Edwards, Anderson, & Meares, 1994;Lapointe, Crayton, DeVito, Fichtner, & Konopka, 2006). Other studies have demonstrated a trend towards lefthemispheric lateralization in non-clinical individuals with inconsistent handedness and high trait dissociation (Ashworth, Ciorciari, & Stough, 2008); a negative relationship between interregional EEG cross-correlation indices and trait dissociation in patients with paranoid schizophrenia (Bob, Susta, Glaslova, & Boutros, 2010); and reduced complexity of the EEG associated with narrowing of attention during interview-assisted evocation of dissociative symptoms in a patient with an anxiety disorder and non-specific encephalopathy due to a motorcycle accident (Bob, Golla, Epstein, Konopka, 2011).…”
mentioning
confidence: 99%